Private Adventure - Hunt, Roderick (Oxford university press, 1986)
Private Adventure" by Roderick Hunt is part of the popular "Oxford Reading Tree" series featuring characters like Biff, Chip, and Kipper. In this story, the children embark on a thrilling adventure when they discover a mysterious item in their backyard.
Keywords: Textbook